104k views
10 votes
What's the y-intercept f(x) = (x+1)(x-9)(x-1)^2

1 Answer

7 votes

Answer:

The y-intercept y = -9

Explanation:

Given the function


f\left(x\right)\:=\:\left(x+1\right)\left(x-9\right)\left(x-1\right)^2

Determining the y-intercept of the function

We know that the value of the y-intercept can be determined by setting x = 0 and determining the corresponding value of y.

so substitute x = 0 in the function


y\:=\:\left(x+1\right)\left(x-9\right)\left(x-1\right)^2


y\:=\:\left(0+1\right)\left(0-9\right)\left(0-1\right)^2


y=1\cdot \left(-9\right)\left(0-1\right)^2


y=1\cdot \left(-9\right)\cdot \:1


y=-1\cdot \:9\cdot \:1


y=-9

Therefore, the y-intercept y = -9

User Don Miguel
by
4.6k points